Co oznacza „godność człowieka”? - Anzenbacher, Arno (Horyzonty Wychowania, 2017)
The reflection upon human dignity taken up by the author wasconcentrated around three issues. The context of the first one islegal-ethical issues, with special emphasis put on the relationsbetween understanding dignity and rights of a human being, bothas an individual-person and as a citizen of a particular community.The second thread of deliberations was determined witha question about the essence of human dignity, with reference tobiblical texts as well as the texts of modern philosophy (Kant,Hegel). The third aspect of dignity was framed by its understandingas a world view basis for contemporary human being.And this is subject to the pluralisation process which, accordingto the author, leads to erosion of essential understanding of thisconcept and risk of ceasing treating it as a basic and universalethical norm protecting every human being.